The impact of autoimmunity-related early ovarian aging on ICSI cycle outcome - Beydilli Nacak, Gulay; Ozkaya, Enis; Yayla Abide, Cigdem; Bilgic, Bulent Emre; Devranoglu, Belgin; Gokcen Iscan, Reyyan (Gynecological endocrinology, 2018)
The aim of this study was to investigate the impact of anti-thyroid peroxidase antibodies (Anti-TPO) on the in vitro fertilization and embryo transfer (IVF-ET) outcome in women with poor ovarian reserve but normal thyrotropin levels. A total of 300 patients with poor ovarian reserve undergoing ICSI cycle from April 2015 to December 2017 were analyzed retrospectively. Subjects were divided into two groups: Group 1: Women with early ovarian aging, Group 2: Women with age related poor ovarian reserve. All subjects underwent anti-thyroid peroxidase antibody (anti-TPO) analysis. The impacts of age and anti-TPO positivity on cycle outcome were assessed. There were no significant differences in basal FSH, basal AMH levels, and antral follicle count between the two main groups. Groups were also comparable in terms of the duration of ovarian stimulation, peak estradiol level, starting gonadotropin dose, total gonadotropin dose, and number of oocytes retrieved. Clinical pregnancy and cycle cancelation rates were significantly higher in group with age-related poor ovarian reserve. While autoimmune thyroid disease rate was significantly higher in group with early ovarian aging. Anti-TPO positivity was a risk factor for poor cycle outcome [RR: 2.8 (95% CI: 1.2-6.3)]. Early ovarian aging may be associated with poorer cycle outcome compared to group with age-related poor ovarian reserve. This difference may be associated with high rate of autoimmunity which led to the impaired endometrial receptivity. 本研究的目的是研究抗甲状腺过氧化物酶抗体（抗-TPO）对卵巢储备不良但促甲状腺激素水平正常女性体外受精-胚胎移植（IVF-ET）结局的影响。我们回顾性分析了2015年4月至2017年12月接受ICSI周期治疗的300例卵巢储备功能不全的患者。受试者分为两组：第1组：卵巢早衰患者, 第2组：年龄相关的卵巢储备功能不全患者。分析所有受试者抗甲状腺过氧化物酶抗体（抗TPO）水平, 评估年龄和抗TPO阳性对周期结果的影响。两组之间的基础FSH, 基础AMH水平和窦卵泡计数没有显著差异。同时比较了两组的卵巢刺激持续时间, 雌二醇峰值水平, 起始促性腺激素水平, 总促性腺激素水平以及卵母细胞回收数量。年龄相关的卵巢储备功能不全组临床妊娠和周期取消率显著升高。卵巢早衰组自身免疫性甲状腺疾病发生率明显增高。抗TPO阳性是不良周期结局的风险因素[RR：2.8（95％CI：1.2-6.3）]。与年龄相关的卵巢储备功能不全组相比卵巢早衰可能与周期结局不良有关。这种差异可能与自身免疫导致的子宫内膜容受性受损有关。